RECONSTRUCTING THE SELF-IDENTITY OF SEXUAL VIOLENCE SURVIVORS THROUGH WRITTEN NARRATIVES FROM AN ISLAMIC PERSPECTIVE - Anita Sari; M.Fahli Zatrahadi; Miftahuddin (AL-TAZKIAH, 2026)
This study aims to examine the role of life narratives in the psychological trauma recovery process of sexual violence survivors, integrating an Islamic perspective as an analytical framework. The study employed a qualitative approach using the Written Narrative Inquiry (WNI) method, collecting data through online written narratives via an open-ended essay questionnaire in Google Forms. Five female sexual violence survivors were selected through purposive sampling with an online snowball sampling technique. The data were analyzed using narrative thematic analysis combined with an Islamic perspective, encompassing the values of patience, tawakkul (trust), ḥ if ẓ al-nafs (relief in the heart), and tazkiyatun nafs (relief in the heart). The results showed that the survivors' narrative patterns progressed from a phase of disorientation to one of acceptance and self-identity reconstruction, with family as the primary source of support. Several respondents showed signs of post-traumatic growth (PTG), namely positive psychological growth after a crisis. The findings also revealed limited access to professional mental health services, with none of the respondents receiving formal psychological support. This study confirms that written narratives composed by survivors themselves can serve as a meaningful tool for emotional recovery. Strengthening survivor-friendly mental health services and developing community-based social support systems are urgently needed to ensure effective and sustainable recovery for victims of sexual violence in Indonesia. The research findings indicate that the values of patience, trust in God, and maintaining self-dignity (ḥifẓ al-nafs) emerge as sources of meaning that help survivors rebuild their self-identity and hope in life, thereby contributing to their psychological recovery through written narratives. The findings of this study can serve as a basis for developing narrative-based support services and Islamic values to facilitate survivors' psychological recovery.